Kajian Pemanfaatan Luas Area Terminal untuk Pendapatan Non-aeronautical di Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Muhamad Albi Ferano (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the potential utilization of empty space on the second floor of the domestic terminal of Zainuddin Abdul Madjid International Airport (ZAM) Lombok to increase revenue from the non-aeronautical sector. The background of this study is based on the importance of optimizing airport assets to support long-term financial sustainability. This is crucial considering that the aeronautical sector is highly dependent on fluctuating flight traffic. Therefore, the development of the non-aerospace sector is a strategic alternative that needs to be seriously addressed. The research method used is descriptive qualitative, with data collection techniques through direct observation on site, interviews with airport management, and documentation studies. The results of the observation indicate that there is an empty space on the second floor of the terminal, specifically between the waiting room and a row of commercial tenants, which has not been optimally utilized. This area is considered to have a strategic position and quite high passenger traffic, so it has the potential to be developed into a new commercial facility. One of the proposed developments is a photobox service business unit with a local Lombok cultural theme. This concept is considered interesting because it combines digital technology with elements of cultural tourism promotion, in line with the trend of tourist needs for documentation and unique experiences. A feasibility analysis was conducted using the Business Model Canvas approach and the 7P marketing strategy (product, price, place, promotion, people, process, and physical evidence). The results showed that this idea is feasible from both an operational and marketing perspective. The study concluded that developing a photo booth business in an empty airport area has the potential to become a new, stable, efficient, and market-relevant source of revenue. Recommendations are given to airport management to immediately realize the utilization of this area to support the airport's role as a regional economic and tourism hub.